Photosynthesis and Respiration of Developing Populus tremuloides Internodes - Brayman, Andrew A. (1982)
The photosynthetic and respiratory performance of developing internodes of Populus tremuloides was evaluated by infrared gas analysis. Anatomical and morphological transitions were related to metabolic activity. Photosynthetic rates ranged from 6.0 to 10.0 milligrams CO(2) per decimeter squared per hour in the youngest internodes to 2.5 to 3.8 milligrams CO(2) per decimeter squared per hour in internodes with fully developed bark tissues. Respiration exceeded the rate of photosynthesis on the average by a factor of two. Stem photosynthesis increased with temperature up to 40°C and declined steeply between 40 and 50°C. Stem respiration increased nearly linearly to temperatures as high as 50°C.